PENANGANAN PERSELISIHAN HASIL PILKADA KOTA SERANG OLEH MAHKAMAH KONSTITUSI - Rahmawati, Nurlaili (Ahkam: Jurnal Hukum Islam, 2018)
The dispute of local election result is related to difference of the way or amount of result in counting vote between local election commission as the institution of administrator’s election and participants of the local election. If only there is participants of local election who are unsatisfied with the result, they can submit the lawsuit to Constitution Court as regulation article 24C UUD 1945. The reason of dispute local election result in  Serang City is due to broken seal of vote voice box, and a lot of cheating done by the couples of candidates but the difference in vote between winners and losers is more than 2%. This research is using case study and descriptive-analysis method. The result is Constitution Court wouldn’t judge the case, if the lawsuit doesn’t comply to formal requisites: first, difference of voting count is not more than 2% of legal vote; second, the lawsuit submitted is not Constitution Court’s authority; third, overdue factor related time of submit lawsuit, as the regulation, should be submitted on 3 (three) days after announcement.Keywords: Local Election Disputes, Constitution Supreme Court